Current Evidence for Developmental, Structural, and Functional Brain Defects following Prenatal Radiation Exposure - Tine Verreet; Mieke Verslegers; Roel Quintens; Sarah Baatout; Mohammed A. Benotmane (Neural Plasticity)
Ionizing radiation is omnipresent. We are continuously exposed to natural (e.g., radon and cosmic) and man-made radiation sources, including those from industry but especially from the medical sector. The increasing use of medical radiation modalities, in particular those employing low-dose radiation such as CT scans, raises concerns regarding the effects of cumulative exposure doses and the inappropriate utilization of these imaging techniques. One of the major goals in the radioprotection field is to better understand the potential health risk posed to the unborn child after radiation exposure to the pregnant mother, of which the first convincing evidence came from epidemiological studies on in utero exposed atomic bomb survivors. In the following years, animal models have proven to be an essential tool to further characterize brain developmental defects and consequent functional deficits. However, the identification of a possible dose threshold is far from complete and a sound link between early defects and persistent anomalies has not yet been established. This review provides an overview of the current knowledge on brain developmental and persistent defects resulting from in utero radiation exposure and addresses the many questions that still remain to be answered.